Domestic violence: Screening and management in South Africa - Deidré Pretorius; Aviva Ruch (South African Family Practice)
Violence manifests in various ways in healthcare, including trauma from an undifferentiated patient, psychosomatic illness, substance abuse or dependency and mental health challenges. Different forms of violence exist, such as intimate partner violence, gender-based violence, domestic violence, child abuse, neglect, elder abuse, sexual violence, self-directed violence and collective violence. These may be included in domestic violence or exist as standalone forms. Health practitioners play a pivotal role in managing incidents of domestic violence. This article highlights the definitions in the Amended Domestic Violence Act of 2021 and suggests screening options for domestic violence. The authors also suggest screening tools, a management flow diagram and contact numbers for resources. Domestic violence can be a generational curse that compromises biopsychosocial wellbeing. To break the perceived culture of violence, healthcare workers play a pivotal role in screening and management, as well as the mandatory reporting of domestic violence when children and the elderly are sharing such a household.